Development of minapolitan area in Bitung City, Indonesia - Onibala, Hernie; Kepel, Rene Charles; Sinjal, Hengky J (Universitas Sam Ratulangi, 2018)
Title (Bahasa Indonesia): Pengembangan Kawasan Minapolitan di Kota Bitung, Indonesia The Ministry of Maritime Affairs and Fisheries has set Bitung City as one of the locations for minapolitan program implementations based capture fisheries. Minapolitan's fisheries Bitung City is a neighborhood-based economic development fishing effort developed in an integrated manner by the government, the privatesectorand community to create a business climate forbetter for regional economic growth, job creation and community income neighborhood Bitung City. This study aimsto analyze the policy strategy for developingMinapolitan Region of the City of Bitung through SWOT analysis and determinepriorities for the development strategy of Bitung city Minapolitan Region. The research method is a survey study, data were collected through interviews and direct observation and literature. SWOT analysis is used to identify strengths, weaknesses, opportunities and threats. Furthermore, to determine the alternative development strategy used OSPM. The study concluded that the strategies that can be used for the development Minapolitan in Bitung are as follows: 1) optimization of fisheriesproduction; 2) improve the facilities, infrastructure and transport infrastructure and fishing port; 3) by improving the quality of human resources in fishing; 4) improving the quality of fisheriesproducts to be able to compete infree market; 5) to build the collective awareness to stay remain committed and consistent in developing minapolitan; 6) industrialization of fisheries bu supportingSpecial Economic Zone (SEZ).Kementerian Kelautan dan Perikanan telah menetapkan Kota Bitung sebagai salah satu lokasi implementasi program minapolitan berbasis perikanan tangkap. Kawasan minapolitan perikanan tangkap di Kota Bitung adalah suatu kawasan pengembangan ekonomi berbasis usaha penangkapan ikan yang dikembangkan secara terintegrasi oleh pemerintah, swasta dan masyarakat untuk menciptakan iklim usaha yang lebih baik untuk pertumbuhan ekonomi wilayah, penciptaan lapangan kerja dan pendapatan masyarakat kawasan Kota Bitung. Penelitian ini bertujuan menganalisis strategi kebijakan pengembangan Kawasan Minapolitan kota Bitung melalui analisis SWOTdan menetapkan prioritas strategi pengembangan Kawasan Minapolitan kota Bitung. Metode penelitian adalah penelitian survei, data dikumpulkan melalui wawancara dan observasi langsung dan literatur. Analisis SWOT digunakan untuk menidentifikasi kekuatan, kelemahan, peluang dan ancaman. Selanjutnya untuk menentukan alternatif strategi pengembangan digunakan OSPM. Hasil penelitian menyimpulkan bahwa strategi yang dapat digunakan untuk pengembangan minapolitan di Bitung sebagai berikut: 1) optimalisasi produksi perikanan; 2) meningkatkan sarana, prasarana dan infrastruktur transportasi dan pelabuhan perikanan; 3) peningkatan kualitas SDM nelayan; 4) peningkatan kualitas produk perikanan untuk dapat berdaya saing dipasar bebas; 5) membangun kesadaran kolektif tetap komitmen dan konsisten dalam mengembangkan minapolitan; 6) industrialisasi perikanan dengan mensuport KEK.